Carbon nanofiber assisted micro electro discharge machining of reaction-bonded silicon carbide - Liew , Pay Jun; Yan , Jiwang; Kuriyagawa, Tsunemoto (2013)
Carbon nanofiber assisted micro electro discharge machining was proposed and experiments were performed on reaction-bonded silicon carbide. The changes in electro discharging behavior, material removal rate, electrode wear ratio, electrode geometry, spark gap, surface finish, surface topography and surface damage with carbon nanofiber concentration were examined. It has been found that the addition of carbon nanofiber not only improves the electro discharge frequency, material removal rate, discharge gap, but also reduces the electrode wear and electrode tip concavity. Bidirectional material migrations between the electrode and the workpiece surface were detected, and the migration behavior was strongly suppressed by carbon nanofiber addition. Adhesion of carbon nanofibers to the workpiece surface occurs, which contributes to the improvement of electro discharge machinability. These findings provide possibility for high-efficiency precision manufacturing of microstructures on ultra-hard ceramic materials.